Assessment of the level of physical fitness of youth of student age in the format of GTO standards - Skotnikova A.V.; Aleksandrova V.A.; Serikova Yu.N.; Ovchinnikov V.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the level of physical fitness of youth of student age 18-19 years old according to the GTO standards. Methods and structure of the study. Boys and girls aged 18-19 years who are not athletes took part in the scientific work. Testing included an assessment according to GTO standards. The All-Russian physical culture and sports complex GTO includes a comprehensive assessment and is the basis for monitoring the physical fitness of the population of various age groups. Results and conclusions. The problem of physical fitness of student-age youth does not lose its relevance from year to year, the obtained testing data according to the GTO standards only confirm this: low level of endurance - 100% of young men will not pass this standard; Of the girls, only 50% will be able to pass the standard; the level of strength abilities of young men according to the standard «pull-ups from hanging on a high bar» is assessed as low - only one of the subjects will be able to pass it; among girls, only 20 people will be able to pass the standard «flexion and extension of the arms while lying on the floor»; according to the standard assessing the level of flexibility, among young men only 2 people were able to fulfill the standard; among girls, 70% were able to pass this standard, but the average value for the group is only 8,8 ± 3,4 cm, which corresponds only to the bronze badge; according to the standing long jump standard among boys, only 30% received a positive result; among girls, 80% have a positive result, however, the average value of 169,5 ± 17,5 cm indicates that they received only a bronze badge.